Effectiveness And Contribution of Hotel Tax And Restaurant Tax To Increasing Local Revenue In Central Halmahera Regency: Hotel Tax And Restaurant Tax To Increasing - Musdar Muhammad; Nurmila Manopo; Nahu Daud (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the contribution of hotel and restaurant taxes to the Local Revenue (PAD) of Central Halmahera Regency for the period 2013-2024. This study uses a descriptive quantitative approach with geometric growth, effectiveness, and contribution analysis methods. The results show that hotel tax revenue has declined, from IDR 108,748,138 in 2019 to IDR 69,251,000 in 2023, with a negative growth of -10.67% per year. The average effectiveness was only 3.40% per year, with a contribution to PAD of 0.26%. Meanwhile, restaurant tax has increased significantly from IDR 188,473,950 in 2019 to IDR 24,826,199,167 in 2023, with a geometric growth rate of 238.78% per year, an average effectiveness of 62.57%, and a contribution to PAD of 26.46%. These findings indicate that restaurant tax is a more potential source of PAD than hotel tax. Therefore, local governments need to evaluate hotel tax targets, improve taxpayer compliance, and develop the tourism and culinary sectors synergistically to optimize regional revenue